Wyzwania dla sekurytyzacji - Kidacka, Izabela (Challenges for Securitization Summary, 2008)
The securitization financial performance depends on all the participants' professional experience level. The originators require experienced investment bankers, lawyers and auditors, while the investors need the confidence, arising from organizers' professional background. All of them rely on opinions of professional and reliable rating agencies. The organizers require the rating agencies' opinions to estimate the transaction support level, while the investors to calculate the emission risk level, regardless of internal investment standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 278-287